2022
DOI: 10.1186/s12978-021-01238-0
|View full text |Cite
|
Sign up to set email alerts
|

Professionalism, stigma, and willingness to provide patient-centered safe abortion counseling and care: a mixed methods study of Ethiopian midwives

Abstract: Background Midwives are a large proportion of Ethiopia’s health care workforce, and their attitudes and practices shape the quality of reproductive health care, including safe abortion care (SAC) services. This study examines how midwives’ conceptions of their professional roles and views on women who have abortions relate to their willingness to provide respectful SAC. Methods This study uses a cross-sectional, mixed methods design to conduct a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Studies exploring the provision of abortion services found that providers might judge the patients based on a variety of factors relating to a religious or moral values or stigma, such as on whether or not the person seeking abortion was married,91 92 raped,41 the duration of her pregnancy and whether she was ‘convincing enough’ in articulating her desire for abortion, whether or not the sexual act that resulted in the pregnancy was socially sanctioned, and if contraception was used 41 43 93 94…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies exploring the provision of abortion services found that providers might judge the patients based on a variety of factors relating to a religious or moral values or stigma, such as on whether or not the person seeking abortion was married,91 92 raped,41 the duration of her pregnancy and whether she was ‘convincing enough’ in articulating her desire for abortion, whether or not the sexual act that resulted in the pregnancy was socially sanctioned, and if contraception was used 41 43 93 94…”
Section: Resultsmentioning
confidence: 99%
“…Many papers explicitly sought to describe and assess the impact of provider religiosity on SRH care, sometimes as their primary research question. In contexts both with and without a formal conscientious objection regime, there were healthcare workers who explicitly said that they objected to abortion on religious grounds and would not provide it 35 43 65 93–97. A study in Malawi documented how this moral or religious objection extended to the provision of postabortion care, with healthcare workers interviewed describing women seeking post abortion care as ‘sinners’ or ‘criminals’ 98…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, social mores and opinions around abortion continue to present barriers to access, even when abortion is legal. Fekadu et al and O’Connell et al address stigma at the provider and community level, exploring barriers that this stigma creates to those seeking abortion care [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%